LELAGON DOLANAN ANAK DAN PENDIDIKAN KARAKTER (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
Children folksongs laras slendro and pelog are full of noble values of national cultures. Nowadays, they are abandoned. Children as the subjects and appreciators of the songs get more unfamiliar with the songs. The songs are less often heard in the family, schools, playground and the place of living environments and other places of gathering for children. The lack of new creation of folksongs worsens the condition. New creation of the songs is badly needed to introduce, preserve, and plant the noble values of national cultures. When the songs and their values can get to more and more children, the character development of the children will be colored with the values of national cultures. They may grow and become generations that respect values of national cultures. Kata kunci: lelagon dolanan anak, pendidikan karakter, pelog dan slendro